Examining the essential conformity of mind and object based on the type of relationship between nature and existence From the perspective of Ayatollah Javadi Amoli and Mesbah Yazdi - Rohollah Adineh; sayyede Roghaye Mosavi (حکمت اسرا)
How the findings of the mind are realized is one of the fundamental issues of epistemology. In the philosophy of Sadr al-Muta'allehin, the realism of the mind is explained in two ways: the essential correspondence between mental existence and external existence and the adaptation of the worlds. On the other hand, due to Sadra's various interpretations of nature, commentators on Sadra's wisdom, including Mesbah Yazdi and Javadi Amoli, have discussed the nature and type of its relationship with existence.Therefore, considering the role of nature and essential concepts in the fact of showing the mind and the criterion of nature for cognition in Sadra's wisdom, the issue of realizing mental existence is also affected by what nature is and the type of its relationship with existence. Now, the main issue of the present study is that based on the type of relationship between nature and existence, in the view of Professor Javadi Amoli and Mesbah Yazdi, based on the originality of existence, the essential conformity of mind and object is possible?After reviewing in the present article by descriptive-analytical method, it was concluded that in the view of Mesbah Yazdi and Javadi Amoli, the nature of mental emergence and the place of nature is only in the mind and there is no research outside, hence the nature Mental refers only to external reality, so the objective correspondence between mental and external nature does not make sense, and in order to prove the reality of mental imaginations, another expression must be provided.